(untitled) (Journal of Peasants’ Rights, 2023)
Development of Punden Rejo rice field ecotourism as a reflection of the awareness and participation of peasents communities in improving the village economy. The spirit in it emphasizes efforts to reduce unemployment problems and increase the empowerment and creativity of local youth who have so far been less involved in village development. The research method uses a qualitative descriptive approach. Research activities consist of: collecting, processing, categorizing, analyzing and presenting data objectively or in accordance with the reality in the field to know and understand sequentially the factors inhibiting the development of Punden Rejo rice field ecotourism and the empowerment efforts made to overcome this . BUMDes and Pokdarwis institutions as ecotourism managers have not fully synergized with peasents communities. These two institutions do not yet have institutional recognition from the local community. For this reason, efforts to raise public awareness are needed which involve community participation so that they are actively involved in supporting and participating in various programs in community empowerment efforts.